PENYELESAIAN VEHICLE ROUTING PROBLEM WITH TIME WINDOWS (VRPTW) MENGGUNAKAN ALGORITMA GENETIKA HYBRID - Diah Anggraeni Pitaloka; Wayan Firdaus Mahmudy; Sutrisno . (Journal of Environmental Engineering and Sustainable Technology, 2014)
Vehicle Routing Problem with Time Windows (VRPTW) is a combinatorial problem which is used to determine the route of a goods distribution from depots (distribution center) to customers scattered in various points of the site. VRPTW is an extension of the VRP with constraints the limitations on the capacity of goods and every customer have time interval of service [ ] or time windows. In this study, the hybrid genetic algorithm with nearest insertion heuristic is used as one of the search alternative solutions. The implementation for this case, 50% initial solution was generated using nearest insertion heuristic method and 50% rest are generated by randomly. This completion is tested in a set of Solomons problem. The results of this study are compared with the best known solution of Solomon using 2 sets of test data from each data type such as C1, C2, R1, R2, RC1, dan RC2 with 25, 50 and 100 customers. The results show that the implementation of hybrid genetic algorithm and the nearest insertion heuristic gives solutions which is nearly optimal or approaching the best known of Solomon for data type C101, C105, C201, R101, RC101 dan RC102.